Alcohol and breast cancer risk: Middle-aged women’s logic and recommendations for reducing consumption in Australia - Meyer, Samantha B.; Foley, Kristen; Olver, Ian; Ward, Paul R.; McNaughton, Darlene; Mwanri, Lillian; Miller, Emma R. (PLOS ONE, 2019)
Background We aimed to understand the factors shaping alcohol consumption patterns in middle-aged women (45–64), and to identify participant-driven population- and policy-level strategies that may be used to addresses alcohol consumption and reduce breast cancer risk. Methods Semi-structured interviews (n = 35) were conducted with ‘middle-aged’ women conversant in English and living in South Australia with no history of breast cancer diagnosis. Data were deductively coded using a co-developed framework including variables relevant to our study objectives. Women were asked about their current level of awareness of the association between alcohol and breast cancer risk, and their personal recommendations for how to decrease consumption in middle-aged Australian women. Results Women discussed their previous efforts to decrease consumption, which we drew on to identify preliminary recommendations for consumption reduction. We identified a low level of awareness of alcohol and breast cancer risk, and confusion related to alcohol as a risk for breast cancer, but not always causing breast cancer. Participants suggested that education and awareness, through various means, may help to reduce consumption. Conclusions Participants’ description of strategies used to reduce their own consumption lead us to suggest that campaigns might focus on the more salient and immediate effects of alcohol (e.g. on physical appearance and mental health) rather than longer-term consequences. Critical considerations for messaging include addressing the personal, physical and social pleasures that alcohol provides, and how these may differ across socio-demographics.